Hell under the rising sun : Texan POWs and the building of the Burma-Thailand death railway - Crager, Kelly E., 1968- (Texas A & M University military history series, 2008)
Late in 1940, the young men of the 2nd Battalion, 131st Field Artillery Regiment stepped off the trucks at Camp Bowie in Brownwood, Texas, ready to complete the training they would need for active duty in World War II. Many of them had grown up together in Jacksboro, Texas, and almost all of them were eager to face any challenge. Just over a year later, these carefree young Texans would be confronted by horrors they could never have imagined." "For more than three years, the Texans, along with the sailors and marines who survived the sinking of the USS Houston, were prisoners of the Imperial Japanese Army. Beginning in late 1942, these prisoners-of-war were shipped to Burma to accelerate completion of the Burma-Thailand railway. These men labored alongside other Allied prisoners and Asian conscript laborers to build more than 260 miles of railroad for their Japanese taskmasters. They suffered abscessed wounds, near-starvation, daily beatings, and debilitating disease. 89 of the original 534 Texans taken prisoner died in the infested, malarial jungles. The survivors received a hero's welcome from Gov. Coke Stevenson, who declared October 29, 1945 as "Lost Battalion Day" when they finally returned to Texas." "Kelly E. Crager consulted official documentary sources of the National Archives and the U.S. Army and mined the personal memoirs and oral history interviews of the "Lost Battalion" members themselves. He focuses on the treatment the men received in their captivity at the different camps they occupied, and surmises that a main factor in the battalion's comparatively high survival rate (84 percent of the 2nd Battalion) was the comradery of the Texans and their commitment to care for each other